Acupuncture and moxibustion as adjunctive therapy for postoperative gastrointestinal dysfunction in gastric cancer: a systematic review and network meta-analysis - Ou, Yangxu; Lin, Dezhi; Ni, Xixiu; Feng, Chengzhi; Rong, Jing; Gao, Xiaoyu; Yu, Yang; Liu, Xinrui; Zhang, Zhiyang; Xiao, Wang; Tang, Zili; Zhao, Ling (Frontiers in Medicine, 2024)
Objectives This study aimed to evaluate and compare the efficacy and safety of different acupuncture and moxibustion techniques as adjunctive therapy in addressing Postoperative gastrointestinal dysfunction (PGD) associated with gastric cancer (GC). Methods Eight medical databases were comprehensively searched for relevant randomized controlled trials (RCTs) as of October 2024. A network meta-analysis (NMA) was performed using frequency models, combining all available direct and indirect evidence from RCTs. Time of first bowel sounds (TFBS) was set as the primary outcome, and time to first defecation (TFD) and time to first flatus (TFF) were set as the secondary outcomes. All outcomes were ranked using surface under the cumulative ranking curve (SUCRA) probabilities to determine a hierarchy of treatments, and the probability that the intervention will be in one of the top ranks increases with a higher SUCRA value. Results With 28 randomized controlled trials (RCTs) and 2,459 patients, 18 of which involved adjuvant acupuncture treatments. NMA based on SUCRA rankings showed that routine care (RC) with acupuncture (ACU), with acupressure (ACUP), with moxibustion (MOX) and acupoint injection (AI) were the top-ranked therapies for shortening TFBS and TFF in patients with GC compared with RC; additionally, RC + MOX + CUP and RC + MOX were the relatively best therapies for TFD. No serious adverse events were reported in the studies assessing the safety of adjunctive acupuncture therapy. Our study found that ST36, ST37, ST39, and PC6 were the most commonly used acupoints for adjuvant acupuncture treatments in treating PGD associated with GC. Conclusion Acupuncture and moxibustion, when used as supplementary therapies, demonstrated efficacy and relative safety in managing PGD associated with GC. The recommended order for adjunctive acupuncture- and moxibustion-related therapies for PGD in patients with GC, in terms of conservativeness, is as follows: RC + ACU, RC + MOX + AI, RC + ACUP, RC + MOX + CUP and RC + MOX. Despite their inclusion, the overall methodological quality of the studies was poor, which need for further high-quality randomized controlled trials to support existing results. Systematic review registration https://www.crd.york.ac.uk/PROSPERO.